Study of children’s health of preschool age - Dolzhykova , Olena; Yeromenko, Rymma; Matviichuk , Olena (ScienceRise: Medical Science, 2023)
A strategically important and priority task of the state in the field of health care is to preserve the life and health of children. The aim is to analyze the state of health of preschool children during 2014-2018 to determine the main diseases and influencing factors. Materials and methods. The analysis of medical records of children aged 2-6 years was carried out in a preschool educational institution (PEI) in the city of Kharkiv (Shevchenkivskyi district) for the period 2014-2018. The analysis was carried out in accordance with the current legislation of Ukraine. Results. The maximum percentage of children with chronic pathology was recorded in 2014. During the next 4 years, a decrease in the percentage of children with pathologies was observed, but this indicator remained at a high level. Among the pathologies, speech defects, whose frequency were recorded, which were evenly distributed among children aged 3-6 years. On the part of the organs of vision, isolated cases of strabismus, astigmatism and hypermetropia were recorded. Pathological conditions of the respiratory system - adenoid vegetations were registered in children aged 4-6 years. The maximum percentage among pathologies was anemia, which was noted more often in children aged 4-5 years. Pathologies of the digestive system - gastritis, hernia, and liver diseases were registered to the maximum in 2014, and then a decrease in their number was observed. Obesity, as a pathology associated with endocrine dysfunction, tended to increase but did not depend on the age of children. During preventive medical examinations, posture disorders and flat feet were more often registered among diseases of the musculoskeletal system. From the genitourinary system, pyelonephritis was registered. Conclusion. A comparison of the morbidity of preschool children revealed an increase in the number of pathologies from the endocrine (obesity), nervous, genitourinary (pyelonephritis) and circulatory systems (anaemia)